Simulating cotton yield response to deficit irrigation with the FAO AquaCrop model - Hussein, F.; Janat, M.; Yakoub, A. (Spanish Journal of Agricultural Research, 2011)
The Food and Agriculture Organization has reflected the importance of predicting yield response to water by developing the AquaCrop model. During three growing seasons (2007-2009), a field experiment was conducted in the South-East of Damascus (Syria) to assess the response of drip irrigated cotton grown under full (FI) and deficit irrigation (80, 65, 50% of FI). Input data and comparisons between simulated and observed canopy cover (CC), biomass production at harvesting, final seed cotton yield, and soil water content using data sets of the 2007 season, were used for model calibration. The calibrated model was validated using data sets of the 2008 and 2009 seasons, getting accurate simulation results for CC [root mean square error (RMSE) = 6.5%] and actual evapotranspiration- ETa (RMSE = 25 mm, index of agreement = 0.99). The predicted seed cotton yields were within 6% of measurements. The model predictions of soil water content in the 0.60 m profile were close in the general trend to the measurements. In spite of the good prediction of ETa and seed cotton yield for each treatment, there is an apparent tendency for AquaCrop to over-estimate water use efficiency (WUE) under water-deficit conditions. Therefore, in cases of limited input data, the AquaCrop could be a promising model for estimating crop productivity under deficit irrigation conditions.